Two-way coupling simulation of interaction between a supersonic flow and a non-rigid plate. Сomparison of numerical and experimental results - Kopysov, Sergey Petrovich; Tonkov, Leonid Evgenievich; Chernova, Alyena Alekseevna (Computational Continuum Mechanics, 2013)
This paper presents algorithms for solving the two-way coupled problem of interaction between a supersonic flow and a non-rigid plate. Several algorithms implementing weak and strong coupling are compared with the available experimental data. A number of different factors affecting the gas flow and the plate shape in a shock tube are analyzed.
Keywords: fluid-structure interaction (FSI); two-way coupling; shock tube; numerical modeling